Pharmacokinetic Evaluation of a DSPE-PEG2000 Micellar Formulation of Ridaforolimus in Rat - Marcus Laird Forrest; Yunqi Zhao; Jody K. Takemoto; Rebecca M. Bertram; Connie M. Remsberg; Neal M. Davies (MDPI AG, 2012)
The rapamycin analog, ridaforolimus, has demonstrated potent anti-proliferative effects in cancer treatment, and it currently is being evaluated in a range of clinical cancer studies. Ridaforolimus is an extremely lipophilic compound with limited aqueous solubility, which may benefit from formulation with polymeric micelles. Herein, we report the encapsulation of ridaforolimus in 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-methoxy-poly(ethylene glycol 2000) (DSPE-PEG2000) via a solvent extraction technique. Micelle loading greatly improved the solubility of ridaforolimus by approximately 40 times from 200 μg/mL to 8.9 mg/mL. The diameters of the drug-loaded micelles were 33 ± 15 nm indicating they are of appropriate size to accumulate within the tumor site via the enhanced permeability and retention (EPR) effect. The DSPE-PEG2000 micelle formulation was dosed intravenously to rats at 10 mg/kg and compared to a control of ridaforolimus in ethanol/PEG 400. The micelle significantly increased the half-life of ridaforolimus by 170% and decreased the clearance by 58%, which is consistent with improved retention of the drug in the plasma by the micelle formulation.